Bankrupt : global lawmaking and systemic financial crisis - Halliday, Terence C. (Terence Charles) (Stanford University Press, 2009)
Through the lens of the Asian Financial Crisis, this book documents how international organizations and national governments crafted legal responses, through corporate bankruptcy reforms, to the fragility of financial markets in East Asia and worldwide.